(untitled) (Sebha University Conference Proceedings, 2022)
The criminal policy in the field of combating corruption crimes has not achieved its objective of protecting society and its members from this type of crime. Despite the criminalization and punishment for it, there are inadequacies in the prevention policy, which leads to the need to conduct scientific studies and research in order to identify defects and defects, and try finding effective scientific solutions to it. The importance of this research is that it shed light on the role and importance of community members in preventing and combating corruption crimes, and activating it in this regard, with the aim of attaining full participation, in a way that contributes to achieving the desired protection for society and its members. This role is important in stopping and avoiding corruption crimes within the scope of the prevention policy. It also has a significant role in confronting and combating these crimes. But this cannot be included in the branches of criminal policy - criminalization, punishment and prevention, because this role differs with the nature of these policies. In some aspects, it can be included within the scope of the prevention policy, as is the case with the role of individuals in putting pressure on state institutions to carry out their functions. However, this role is an important component of the accounting system and falls within its scope.